Electrochemical detection method of dopamine

By loading SnS2 quantum dots on Zn-MOF and combining gold nanoparticles and dopamine aptamer single chains, Apt/AuNPs/SnS2QDs@Zn-MOF complex was constructed, and the high sensitivity and selective detection of dopamine was achieved using ECL technology, solving the problem of insufficient detection complexity and accuracy in the prior art.

CN119643665AActive Publication Date: 2025-03-18JIANGXI NORMAL UNIV

Patent Information

Application Number
CN202510173725.9
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-02-18
Publication Date
2025-03-18
Estimated Expiration
2045-02-18

AI Technical Summary

Technical Problem

The existing dopamine detection methods have problems such as complexity, high cost, strict equipment requirements and unstable results, and the existing electrochemiluminescence technology still has room for improvement in accuracy and operational complexity.

Method used

By loading SnS2 quantum dots on Zn-MOF, SnS2QDs@Zn-MOF complex is formed, and gold nanoparticles and dopamine aptamer single chains are combined to construct Apt/AuNPs/SnS2QDs@Zn-MOF complex, and high sensitivity and selective detection of dopamine are achieved using electrochemical chemiluminescence (ECL) technology.

Benefits of technology

High sensitivity and selective detection of dopamine are achieved. The ECL intensity and the logarithm of dopamine concentration are linearly related within a certain range, and have the advantages of a wide linear range and a low detection line.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119643665A_ABST
    Figure CN119643665A_ABST
Patent Text Reader

Abstract

The invention discloses an electrochemical detection method of dopamine, and belongs to the technical field of analysis. According to the method, SnS2 quantum dots are loaded on Zn-MOF and modified on an electrode, then gold nanoparticles and a sulfydryl-containing dopamine aptamer single chain are sequentially fixed on the electrode, an Apt / AuNPs / SnS2QDs (at) Zn-MOF / GCE composite electrode (in an open state) is formed, an electrochemical signal of the composite electrode is greatly improved, and based on specific recognition between dopamine and an aptamer chain, the electrochemical performance of the composite electrode is improved. A large cavity of Zn-MOF is used for packaging SnS2 quantum dots with excellent electrochemical properties, electrochemical signal amplification is achieved, when a target object dopamine exists, dopamine can quench an ECL signal, an electric signal is obviously reduced (in a closed state), and therefore a linear relation between the change of the electrochemical signal and the concentration of dopamine is constructed, and the electrochemical property of the electrochemical signal is improved. Therefore, high-sensitivity and high-selectivity detection of dopamine is realized.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to a dopamine detection method, in particular to an electrochemical detection method of dopamine, and belongs to the technical field of analysis and detection. Background Art

[0002] Dopamine, a catecholamine neurotransmitter, plays a key role in many physiological processes and is a neurotransmitter that affects motivation, behavior, learning, memory and other cognitive functions. The clinical level in human body fluids is extremely low, with a normal concentration range of 10 -8 Up to 10 -6 mol / L. As a neurotransmitter, dopamine plays a role in the brain and central nervous system (CNS), and disorders of these systems are associated with a variety of diseases including schizophrenia, depression, and Parkinson's disease. Therefore, it is crucial to develop a simple and sensitive method to quantitatively measure dopamine levels, which is essential for diagnostic purposes and the study of related diseases.

[0003] A variety of techniques and methods have been developed for the quantitative analysis of dopamine, including electrochemical methods, fluorescence methods, chromatography, colorimetry, and even capillary electrophoresis, etc. However, each method has its limitations, including complexity, high cost, strict equipment requirements, and unstable results.

[0004] Compared with traditional dopamine detection methods, electrochemiluminescence (ECL) technology has many unique advantages, such as no need for excitation light source, high cost-effectiveness and small background signal. ECL technology has been widely used in medical diagnosis and environmental monitoring. Its ECL signal originates from the electron transfer between electroactive substances on the electrode surface. For example, the literature (“Ultrasensitiveelectrochemiluminescence biosensor for dopamine based on ZnSe, grapheneoxide@multi walled carbon nanotube and Ru(bpy) 3 2+ ”, L. Tian et al., Sensors and Actuators B: Chemical, 286 (2019) 266-271.) proposed a novel nanostructured carbon nanotube based on ZnSe, graphene-walled carbon nanotubes and Ru(bpy) 3 2+ The dopamine ultrasensitive electrochemiluminescent biosensor is used to detect dopamine, but this method has low accuracy and complicated operation. 2The technology of using QDs to achieve signal amplification to construct an ECL biosensor for dopamine determination is reported. Summary of the invention

[0005] In view of the defects of the prior art, the present invention aims to provide an electrochemical detection method for dopamine. The dopamine detection method is not for the purpose of diagnosing and treating diseases, but aims to overcome the shortcomings and defects of the prior art methods for detecting dopamine. The method is based on SnS 2 The excellent ECL properties of quantum dots and the large cavity characteristics of Zn-MOF are combined to form SnS 2 QDs@Zn-MOF, while utilizing the dopamine quenching effect to form an "ON-OFF" strategy, and utilizing gold nanoparticles combined with dopamine aptamer single chains to improve the selectivity for dopamine, thereby achieving highly sensitive and selective electrochemical detection of dopamine.

[0006] In order to achieve the above technical objectives, the present invention provides an electrochemical detection method for dopamine, which comprises the following steps:

[0007] 1) SnS 2 Quantum dots are loaded onto Zn-MOF to obtain SnS 2 QDs@Zn-MOF; the SnS 2 After QDs@Zn-MOF was dispersed in water, it was dropped onto the electrode surface and dried at room temperature;

[0008] 2) Then, the gold nanoparticle dispersion and the thiol dopamine aptamer single chain solution are sequentially added to the electrode surface of step 1) and incubated for I to form Apt / AuNPs / SnS on the electrode surface. 2 QDs@Zn-MOF composite;

[0009] 3) Modify Apt / AuNPs / SnS 2 The electrode of QDs@Zn-MOF composite was 2 S 2 O 8 ECL test was carried out in PBS solution to obtain the ECL intensity response value;

[0010] 4) A series of standard dopamine solutions with different concentrations were added dropwise to the modified Apt / AuNPs / SnS 2 The electrode surface of the QDs@Zn-MOF complex is incubated II, and then the ECL test is performed according to step 3) to obtain a series of ECL intensity response values, and a standard curve between dopamine concentration and ECL intensity response value is constructed;

[0011] 5) Substituting the dopamine solution to be tested for the standard dopamine solution in step 4) for the ECL test, obtaining the corresponding ECL intensity response value, and calculating the concentration of the dopamine solution to be tested according to the standard curve.

[0012] The key to the technical solution of the present invention is to achieve high-sensitivity and high-selectivity electrochemical detection of dopamine by constructing a biosensor with electrochemical signal response. First, tin disulfide quantum dots (SnS 2 QDs) were encapsulated into a zinc-based metal-organic framework (Zn-MOF) to synthesize SnS with significantly enhanced photoelectric signals. 2 QDs@Zn-MOF composites can significantly enhance the photocurrent intensity and improve the detection sensitivity. 2 QDs@Zn-MOF composite was modified on the surface of glassy carbon electrode (GCE). Then, SnS 2 Gold nanoparticles (AuNPs) were added to the QDs@Zn-MOF coated electrodes because the gold atoms on their surface can bind to the single-chain aptamer containing thiodopamine by forming Au-S bonds. Finally, the single-chain aptamer containing thiodopamine was bound to the surface of AuNPs, and the dopamine aptamer was used to improve the selectivity for dopamine to construct an aptamer sensor. As expected, SnS 2 QDs@Zn-MOF / S 2 O 8 2- The system exhibited good electrochemiluminescence (ECL) response and good selectivity to dopamine (DA). When dopamine was present, the SnS 2 QDs@Zn-MOF / S 2 O 8 2- The ECL signal of the system dropped sharply, so that electrochemiluminescence detection of dopamine could be achieved based on the linear relationship between the ECL intensity and the logarithm of the dopamine concentration within a certain range.

[0013] As a preferred solution, the SnS 2 QDs@Zn-MOF was prepared by the following method: Zn-MOF was ultrasonically dispersed in water, and SnS 2 The quantum dots are subjected to ultrasonic treatment for 5 to 15 minutes, stirred for 6 to 18 hours, centrifuged and dried to obtain the SnS 2 The specific preparation method of QDs@Zn-MOF is as follows: Zn-MOF powder is dissolved in water, ultrasonically treated for 10 min, and SnS 2The QDs solution was added to the above solution, ultrasonicated for 10 min, and magnetically stirred overnight. Finally, the product was centrifuged, washed three times with deionized water, and dried at 60°C overnight. 2 QDs@Zn-MOF nanocomposite, the Zn-MOF synthesized in the present invention has a typical flower-like structure and a large specific surface area, which is more conducive to encapsulating more SnS 2 QDs, compared with the photoelectric signal of Zn-MOF alone, SnS 2 The photoelectric signal of the QDs@Zn-MOF composite is significantly enhanced because Zn-MOF has many large cavities that can load SnS with excellent optical properties. 2 Quantum dots can significantly increase the photocurrent intensity and improve the detection sensitivity.

[0014] As a preferred solution, the SnS 2 The quantum dots were prepared by the following method: SnCl 4 ·5H 2 O and cysteine ​​are dissolved in water to form a precursor solution, and the precursor solution is transferred into a high-pressure reactor for hydrothermal reaction to obtain SnS. As a preferred solution, the hydrothermal reaction conditions are: at a temperature of 160°C to 200°C for 4 to 8 hours. 2 For example, the preparation method of quantum dots is as follows: 2 Add 2.1 g SnCl 4 ·5H 2 O and 2.423 g of cysteine ​​to form a precursor solution, then the mixture was placed in a 50 mL Teflon-lined stainless steel autoclave and heated at 180 ° C for 6 hours. After the mixture was naturally cooled to room temperature, the reaction residue was removed by centrifugation to obtain a yellow supernatant. SnS 2 Quantum dots are nanoscale and have good optical properties, which can significantly enhance the photoelectric signals of Zn-MOF.

[0015] As a preferred solution, the Zn-MOF is prepared by the following method: a zinc acetate aqueous solution and K 4 The PTC aqueous solution is mixed and reacted in the dark until an orange precipitate is formed, which is then centrifuged, washed and dried to obtain Zn-MOF. 4 PTC aqueous solution, and keep it away from light for several days until an orange precipitate is obtained. After centrifugation, deionized water washing and freeze drying, the orange powder is represented as Zn-MOF. The Zn-MOF prepared by this method has a special flower-like structure and has many large cavities, which can better load SnS 2 Quantum dots.

[0016] As a preferred solution, the concentration of gold nanoparticles in the gold nanoparticle dispersion is 0.5-1.5 mM. The concentration of the thiol-containing dopamine aptamer single chain in the thiol-containing dopamine aptamer single chain solution is 4-6 μM. The drop volumes of the gold nanoparticle dispersion and the thiol-containing dopamine aptamer single chain solution on the electrode surface are 8-12 μL and 8-12 μL, respectively. The concentration of the thiol-containing dopamine aptamer single chain directly affects the ECL intensity. At an appropriate concentration of the thiol-containing dopamine aptamer single chain, the appropriate amount of the thiol-containing dopamine aptamer single chain bound to the nanogold particles can make the signal value of the composite electrode reach the most stable.

[0017] As a preferred solution, the incubation conditions of I are: reacting at a temperature of 30-40° C. for 0.5-1.5 hours. Incubation I mainly combines the single-chain aptamer containing thiol dopamine with gold nanoparticles. Gold nanoparticles act as a coreaction accelerator.

[0018] As a preferred embodiment, the K-containing 2 S 2 O 8 K in PBS solution 2 S 2 O 8 The concentration of K is between 9 and 12 mM, and the pH of the PBS solution is between 7.0 and 8.0. 2 S 2 O 8 PBS solution, specifically containing 10 mM K 2 S 2 O 8 of 0.1 M PBS solution.

[0019] As a preferred solution, the incubation conditions II are: reacting at a temperature of 30-40° C. for 30-50 minutes.

[0020] As a preferred solution, the conditions of the ECL test are: the test voltage is -1.8 V to 0 V. As a more preferred solution, the scanning rate of ECL data acquisition is 300 mV / s, and the voltage of the photomultiplier tube (PMT) is 800 V.

[0021] The DNA sequence of the single-stranded aptamer containing thiol dopamine of the present invention is: 5′-SH-(CH 2 ) 6 -GTC TCT GTGTGC GCC AGA GAC ACT GGG GCA GAT ATG GGC CAG CAC AGA ATG AGG CCC-3′. It is a commercial product.

[0022] The present invention relates to K 4 PTC was prepared by the following method: 5 g of perylene tetracarboxylic acid dianhydride (PTCDA) was added to 100 ml of potassium hydroxide aqueous solution (5 g KOH) and kept at 130 °C for 12 hours. Then, the solution was dropped into 500 ml of ethanol to obtain a yellow precipitate. After that, the yellow precipitate was washed several times with ethanol to remove the reducing agent OH. - , and dried under reduced pressure at 40 °C to obtain a yellow powder, denoted as K 4 PTC.

[0023] The gold nanoparticle dispersion of the present invention is prepared by the following method: HAuCl 4 The solution was heated to boiling and then C 6 H 5 Na 3 O 7 ·2H 2 O solution was stirred and refluxed until the solution turned into wine red, and then continued to stir and cool to obtain a gold nanoparticle dispersion. The preparation method of the gold nanoparticles is as follows: 50 mL HAuCl 4 The solution (1.0 mM) was heated to boiling, and then 5 mL of C 6 H 5 Na 3 O 7 ·2H 2 O solution (38.8 mM) and stirred at reflux for 10 min until the solution turned wine red, then turned off the heat source, stirred for 15 min, cooled to obtain Au NPs dispersion, and stored at 4 °C in the dark for later use.

[0024] The SnS 2 QDs@Zn-MOF composite can significantly improve the ECL signal intensity. 2 QDs@Zn-MOF composite synthesis method For example: Dissolve Zn-MOF powder in H 2 O, ultrasonically treated for 10 min, and then SnS 2 QDs(SnS 2 The solution of quantum dots was added to the above solution, and the mixture was ultrasonicated for 10 min and magnetically stirred overnight. Finally, the product was centrifuged, washed three times with deionized water, and dried at 60 °C overnight.

[0025] The SnS 2 For example, the preparation method of QDs is as follows: 2 Add 2.1g SnCl 4 ·5H 2O and 2.423 g of cysteine ​​to form a precursor solution, then, the mixture was placed in a 50 mL Teflon-lined stainless steel autoclave and heated at 180 ° C for 6 hours. After the mixture was naturally cooled to room temperature, the reaction residue was removed by centrifugation to obtain a yellow supernatant.

[0026] The present invention quenches the ECL signal by binding the target (dopamine) to DA-Apt, resulting in a decrease in ECL intensity. The greater the dopamine concentration, the weaker the ECL intensity. The ECL intensity and the logarithm of the dopamine concentration are linearly related within a certain range, thereby quantifying the target dopamine.

[0027] The electrochemical detection method of photodopamine provided by the present invention comprises the following specific steps:

[0028] (1) Construction of electrochemical biosensor: First, a glassy carbon electrode (GCE, 3 mm in diameter) was coated with 0.3 and 0.05 μm Al 2 O 3 The powder was polished to achieve a mirror-like interface, and then the electrode was sonicated in ultrapure water and ethanol and finally dried thoroughly under a nitrogen atmosphere. 2 @Zn-MOF was modified onto the GCE surface (5 mg / mL) and then 2 10 μL of freshly prepared gold nanoparticles were added to the Zn-MOF-coated electrode to obtain AuNPs / SnS 2 Finally, 5 μL of dopamine aptamer (5 μM) was added dropwise onto the electrode to fix the aptamer via the Au-S bond formed between the aptamer and Au NPs, and finally Apt / AuNPs / SnS 2 @Zn-MOF composite electrode.

[0029] (2) Dopamine electrochemical detection: Take 10 μL of SnS 2 @Zn-MOF (5 mg / mL) was dropped onto GCE and dried at room temperature. Then, 10 μL of AuNPs solution (1 mM) was added to SnS 2 @Zn-MOF / GCE electrode, then 10 μL Apt solution (5 μM) was added and dried before use. A three-electrode system was used in an aqueous solution containing 0.1 mM K 2 S 2 O 8ECL measurements were performed in a PBS (pH 7.4) solution in the voltage range of -2.0 V to 0 V. ECL data acquisition was performed at a scan rate of 300 mV / s and a photomultiplier tube (PMT) voltage of 800 V. Dopamine can quench the ECL signal, resulting in a decrease in ECL intensity. The higher the dopamine concentration, the weaker the ECL intensity. The logarithm of the ECL intensity and the dopamine concentration is linearly related within a certain range, thereby quantifying the target dopamine.

[0030] SnS of the present invention 2 The specific preparation method of QDs@Zn-MOF dispersion is as follows: 5 mg of SnS 2 QDs@Zn-MOF powder was ultrasonically dispersed in 1 mL of ultrapure water.

[0031] Compared with the prior art, the technical solution of the present invention brings the following beneficial technical effects:

[0032] 1) The present invention adopts K 4 The flower-like Zn-MOF material prepared by PTC has many large cavities, which effectively loads SnS 2 quantum dots, thus forming SnS 2 QDs@Zn-MOF composite, SnS 2 Quantum dots themselves are excellent optoelectronic materials. Loading them on Zn-MOF can further improve the utilization rate of ECL emitters. Combining the two can significantly increase the photocurrent intensity.

[0033] 2) The present invention achieves highly selective capture of DA through specific recognition of DA and aptamer single chain, and directly uses the quenching effect of dopamine to quench the high ECL SnS 2 The electrochemical signal of QDs@Zn-MOF dropped significantly, and the greater the Mal concentration, the weaker the ECL intensity, thus constructing the relationship between Mal concentration and ECL signal.

[0034] 3) The present invention combines SnS 2 QDs@Zn-MOF 2 Good ECL properties and DA quenching effect to achieve highly sensitive ECL detection of DA.

[0035] 4) The signal amplification electrochemiluminescence sensing strategy for DA constructed in the present invention has a good linear relationship between the ECL intensity and the logarithm of the target concentration in the concentration range of 0.0001~100μM, and has the advantages of a wide linear range and a low detection line. BRIEF DESCRIPTION OF THE DRAWINGS

[0036] Figure 1 This is a schematic diagram of the principle of electrochemiluminescence detection of dopamine in the present invention.

[0037] Figure 2 A and B are scanning electron microscopy images of Zn-MOF; C and D are SnS 2 Scanning electron microscope image of QDs@Zn-MOF.

[0038] Figure 3 A is the energy spectrum of Zn-MOF material; B is SnS 2 Energy spectrum of QDs@Zn-MOF composite.

[0039] Figure 4 The test results of Example 1 for the standard sample, A: the detection target concentration and the corresponding photocurrent response curve of Example 1, B: the logarithmic linear graph of the photocurrent response value and the detection target concentration of Example 1; C: the selectivity investigation results of Example 1.

[0040] Figure 5 A in the formula contains K 2 S 2 O 8 K in PBS solution 2 S 2 O 8 Concentration and ECL signal relationship curve; B is the K-containing 2 S 2 O 8 A is the relationship curve between the pH value of the PBS solution and the ECL signal; C is the relationship curve between the aptamer concentration and the ECL signal; D is the relationship curve between the incubation time of the composite electrode and DA and the ECL signal. DETAILED DESCRIPTION

[0041] The content of the present invention is further described in detail below through specific implementation examples, but this should not limit the protection scope of the claims of the present invention.

[0042] Condition optimization experiment: In order to obtain the best performance analysis of this method, several important experimental conditions were optimized (refer to Example 1 for specific operation steps)

[0043] (1) Exploring K 2 S 2 O 8 The effect of the concentration on the ECL intensity is shown in Figure 5 Middle A:K 2 S 2 O 8 The ECL response curves corresponding to the concentration range of 2~12mM show that the signal value reaches the optimal value when the concentration is 10mM.

[0044] (2) Investigate the effect of pH on ECL intensity: The signal was measured in the pH range of 5.0-9.0. The specific results are as follows: Figure 5A: ECL response curve corresponding to PBS solution in the pH range of 5.0~9.0. It was found that the signal value reached the optimal value when the pH was 7.4.

[0045] (3) To explore the effect of aptamer concentration on ECL intensity, see Figure 5 Middle C: K 2 S 2 O 8 The ECL response curve corresponding to the concentration range of 0~10μM. It was found that when the concentration was 5μM, the signal value reached the most stable and was the most suitable value.

[0046] (4) The effect of dopamine capture reaction time on ECL intensity was investigated in the range of 0–50 min. Figure 5 Middle D: The effect of the reaction time of dopamine capture on the ECL intensity in the range of 0~50 min. The optimal reaction time is 40 min.

[0047] The following example conditions are all carried out under optimal conditions:

[0048] Example 1

[0049] (1) Add 50 mL HAuCl 4 The solution (1.0 mM) was heated to boiling, and then 5 mL of C 6 H 5 Na 3 O 7 ·2H 2 O solution (38.8 mM) and stirred at reflux for 10 min until the solution turned wine red. Turn off the heat source, stir for 15 min, cool to obtain Au NPs dispersion, and store at 4 °C in the dark for later use.

[0050] (2) SnS 2 QDs were prepared according to existing literature. Briefly, SnCl 4 ·5H 2 O (6.0 mM) and L-cysteine ​​(20 mM) were added to 25 mL of water, and then the reaction solution was heated at 180°C for 6 h in a 50 mL Teflon-lined stainless steel autoclave. After natural cooling to room temperature, the reaction residue was removed after centrifugation to obtain a yellow supernatant.

[0051] (3) Zn-MOF powder (25 mg) was dissolved in 5 mL of water and subjected to ultrasonic treatment for 6 h. Subsequently, 5 mL of SnS prepared in step (2) was added. 2The QD solution was added to the above reaction solution and subjected to ultrasonic treatment for 10 minutes, followed by magnetic stirring overnight. The mixture was then separated by centrifugation, washed three times with deionized water, and dried at 60°C overnight.

[0052] (4) Prepare DA-apt with Tris-HCl buffer solution to the corresponding concentration (the specific preparation method and amount are on the purchased test tube bottle). Prepare 10 μL of dopamine of different concentrations (0.0001~100 μM).

[0053] (5) Using 0.3 μm and 0.05 μm Al 2 O 3 The glassy carbon electrode (GCE, 3 mm in diameter) was powder-polished to a mirror-like surface, then sonicated in ultrapure water and ethanol, and finally in N 2 First, 10 μL of SnS prepared in step (3) was added 2 QDs@Zn-MOF was modified onto the GCE surface and dried at room temperature to obtain SnS 2 QDs@Zn-MOF / GCE. Then, 10 μL of gold nanoparticles prepared in step (1) were dropped onto the SnS 2 AuNPs / SnS was obtained on the QDs@Zn-MOF coated electrode. 2 Finally, 5 μL of thiol-containing dopamine aptamer (5 μM) was dropped onto the electrode to immobilize the aptamer by forming Au-S bonds between the aptamer and AuNPs.

[0054] (6) 10 μL of dopamine at different concentrations was dropped onto the electrode and kept reacting at 37°C for 40 min to finally obtain DA / AuNPs / SnS 2 QDs@Zn-MOF / GCE electrode.

[0055] (7) In the presence of 10 mM K 2 S 2 O 8 ECL measurements were performed in a PBS (pH 7.4) solution in the voltage range of -1.8 V to 0 V. ECL data acquisition was performed at a scan rate of 300 mV / s and a photomultiplier tube (PMT) voltage of 800 V. The higher the DA concentration, the weaker the ECL intensity, and there is a definite relationship between the ECL intensity and the DA concentration, thereby achieving sensitive detection of DA; the test solution was used instead of the DA standard solution for the above test, and the concentration results were obtained through the standard curve.

[0056] Example 1 The DNA sequence of the thiol dopamine aptamer [purchased from Sangon Biotech (Shanghai) Co., Ltd.] is as follows:

[0057]

[0058] Figure 1 The AuNPs / SnS 2 Schematic diagram of the principle and process of electrochemiluminescence detection of dopamine by QDs@Zn-MOF / GCE electrode. Figure 2 Zn-MOF and SnS 2 The scanning electron microscopy image of QDs@Zn-MOF material shows that the synthesized Zn-MOF exhibits a uniform nanoflower morphology with an average diameter of about 18 μm. 2 Upon loading onto Zn-MOF, a slight increase in the diameter of the material was observed. Figure 3 The EDS graph shows that SnS 2 Coexistence of C, O, Zn, Sn, and S elements in QDs@Zn-MOF nanospheres. Figure 4 The results of the standard sample test in Example 1 are as follows: Figure 4 B shows that within the dopamine concentration range of 0.0001~100 μM, there is a good linear relationship between the ECL intensity and the logarithm of the target concentration. In addition, in order to prove the practical applicability of this invention in life, the present invention also investigated the specificity and selectivity of this method for dopamine, and selected ascorbic acid (AA), glucose (GLU) and glutathione (GSH) as interferents. The experimental results show that there is no significant difference between the ECL intensity of high-concentration interferents and the ECL intensity of blank samples. Therefore, this method for DA detection has good selectivity and specificity ( Figure 4 C).

[0059] The above description is only the best embodiment of the present invention. All equivalent changes and modifications made according to the scope of the patent application of the present invention should fall within the scope of the present invention.

Claims

1. A method for electrochemical detection of dopamine, characterized in that: The following steps are involved: 1) Loading SnS2 quantum dots onto Zn-MOF to obtain SnS2QDs@Zn-MOF; after dispersing the SnS2QDs@Zn-MOF in water, dripping it onto the electrode surface, and drying it at room temperature; 2) Then, the gold nanoparticle dispersion and the thiol dopamine aptamer single chain solution are sequentially added to the electrode surface of step 1) for incubation I to form an Apt / AuNPs / SnS2QDs@Zn-MOF complex on the electrode surface; 3) The electrode modified with Apt / AuNPs / SnS2QDs@Zn-MOF composite was subjected to ECL test in PBS solution containing K2S2O8 to obtain the ECL intensity response value; 4) A series of standard dopamine solutions of different concentrations were added dropwise to the electrode surface of the modified Apt / AuNPs / SnS2QDs@Zn-MOF composite for incubation II, and then an ECL test was performed according to step 3) to obtain a series of ECL intensity response values, and a standard curve between dopamine concentration and ECL intensity response value was constructed; 5) Substituting the dopamine solution to be tested for the standard dopamine solution in step 4) for the ECL test, obtaining the corresponding ECL intensity response value, and calculating the concentration of the dopamine solution to be tested according to the standard curve.

2. The electrochemical detection method of dopamine according to claim 1, characterized in that: The SnS2QDs@Zn-MOF is prepared by the following method: ultrasonically dispersing Zn-MOF in water, adding SnS2 quantum dots, continuing ultrasonic treatment for 5 to 15 minutes, stirring for 6 to 18 hours, centrifuging and drying to obtain the SnS2QDs@Zn-MOF.

3. The electrochemical detection method of dopamine according to claim 1 or 2, characterized in that: The SnS2 quantum dots are prepared by the following method: SnCl4·5H2O and cysteine ​​are dissolved in water to form a precursor solution, and the precursor solution is transferred into a high-pressure reactor for hydrothermal reaction to obtain the SnS2 quantum dots.

4. The electrochemical detection method of dopamine according to claim 3, characterized in that: The conditions of the hydrothermal reaction are: reacting at a temperature of 160° C. to 200° C. for 4 to 8 hours.

5. The electrochemical detection method of dopamine according to claim 1, characterized in that: The Zn-MOF is prepared by the following method: a zinc acetate aqueous solution and a K4PTC aqueous solution are mixed to react in the dark until an orange precipitate is formed, and then the mixture is centrifuged, washed and dried to obtain the Zn-MOF.

6. The electrochemical detection method of dopamine according to claim 1, characterized in that: The concentration of the gold nanoparticles in the gold nanoparticle dispersion is 0.5-1.5 mM; The concentration of the thiodopamine-containing aptamer single chain in the thiodopamine-containing aptamer single chain solution is 4-6 μM; The drop volumes of the gold nanoparticle dispersion and the thiol-containing dopamine aptamer single-chain solution added onto the electrode surface are 8-12 μL and 8-12 μL, respectively.

7. The electrochemical detection method of dopamine according to claim 1 or 6, characterized in that: The incubation conditions of I are: reacting at a temperature of 30-40° C. for 0.5-1.5 hours.

8. The electrochemical detection method of dopamine according to claim 1, characterized in that: The concentration of K2S2O8 in the K2S2O8-containing PBS solution is in the range of 9-12 mM, and the pH of the PBS solution is in the range of 7.0-8.

0.

9. The electrochemical detection method of dopamine according to claim 1, characterized in that: The conditions of the incubation II are: reacting at a temperature of 30-40° C. for 30-50 minutes.

10. The electrochemical detection method of dopamine according to claim 1, characterized in that: The ECL test conditions are: the test voltage is -1.8 V to 0 V.

Citation Information

Patent Citations

  • Preparation method and application of electrochemical aptamer sensor for detecting dopamine (DA)

    CN103675076A

  • Preparation of Ni-doped stannic oxide formaldehyde sensitive composite material based on ZIF-8 metal organic framework template, product and application

    CN112479246A

  • Double-potential electrochemical luminescence immunosensor and application thereof

    CN116223790A

  • Sensor devices comprising a metal-organic framework material and methods of making and using the same

    US20160231233A1

Cited By

  • Electrochemiluminescence biosensor based on functionalized nuclear track membrane and application of electrochemical luminescence biosensor in dopamine detection

    CN120446506A

  • Flexible supercapacitor

    CN121011455A